A rapid polymerase chain reaction technique for detecting M tuberculosis in a variety of clinical specimens. Issue 12 (December 1998) - Kearns, A M; Freeman, R; Steward, M; Magee, J G
Abstract : A rapid in-house polymerase chain reaction (PCR) assay is described for the direct detection of Mycobacterium tuberculosis complex in clinical material. Its performance is compared with two kit based systems. The results of the in-house assay were comparable with the commercial assays, detecting M tuberculosis in 100% of smear positive, culture positive samples. The in-house assay proved to be rapid, easy, and inexpensive to perform, and the inclusion of an internal inhibitor control permitted validation of the PCR results.